THE EFFECT OF ANTIRETROVIRAL DRUGS ON CARBOHYDRATE METABOLISM - Barno Kh. Shagazatova; Feruza S. Mirxaydarova (Central Asian Journal of Medicine, 2022)
It’s no secret that with the development of information technology, many ethical problems of biom Human immunodeficiency virus infection is one of the most common diseases on earth. The use of antiretroviral therapy in patients with this infection prolongs the life of patients and reduces the risk of serious complications. However, this category of patients has cases of type 2 diabetes mellitus, which is associated with the natural course of the disease and the use of antiretroviral therapy. In our study, we studied the cases of carbohydrate metabolism and insulin resistance in patients with human immunodeficiency virus.